Client Satisfaction Survey - Gateway of Quality Care: Mixed Type Study from a Tertiary Care Centre of Ahmedabad, Gujarat - Rashmi Sanjay Sharma; Gneyaa Shirish Bhatt; Bharat H Patel (Medsci Publications, 2019)
Background: Client satisfaction surveys integral part of quality improvement at a health facility, help in preparing action plan to identify the causes of low satisfaction and steps to maximize patient satisfaction. Aims of this study were to (1) explore level of client satisfaction,(2) find out the reasons of low satisfaction and (3) suggest feasible means for improvement. Methodology: A mixed type of study with both quantitative and qualitative components was undertaken after permission from the head of institute. A total421 (124 OPD & 297 IPD) patient's satisfaction survey forms filled during 2015 - 2016 were analyzed. In order to get more insight and as part of qualitative research, 2 focus group discussions (FGDs) of treated/ discharged patients from IPD and1 for OPD cases were conducted in early 2017. Results: Most respondents during client survey, expressed satisfaction over, cleanliness, security, parking facilities andbehavior of hospital staff. Half of the participants were aware of their rights. More than 25% waited for less than 10 minutes for their registration. However, none of the participants could see concerned care provider within 30 minutes of registration. In FGDs too, most participants mentioned free of cost services, good behavior of doctor, satisfactory treatment and cleanliness of hospital as reasons for choosing this hospital. Conclusion: While survey findings are largely flattering to the system, those from FGDs pointed out certain areas of improvement. Hence, it is recommended to include FGDs, as a part of current client satisfaction survey. Grievance redressal system must be in place in the form of mail boxes installed at hospital. The observations of the survey were shared with all the stakeholders to find out realistic solutions.